Low Double-Negative CD3+CD4−CD8− T Cells Are Associated with Incomplete Restoration of CD4+ T Cells and Higher Immune Activation in HIV-1 Immunological Non-Responders - Lu, Xiaofan; Su, Bin; Xia, Huan; Zhang, Xin; Liu, Zhiying; Ji, Yunxia; Yang, Zixuan; Dai, Lili; Mayr, Luzia M.; Moog, Christiane; Wu, Hao; Huang, Xiaojie; et al. (Frontiers in Immunology, 2016)
Failure of immune reconstitution increases the risk of AIDS or non-AIDS related morbidity and mortality in HIV-1-infected patients. CD3+CD4-CD8- T cells, which are usually described as double negative (DN) T cells, display CD4-like helper and immunoregulatory functions. Here, we have measured the percentage of DN T cells in the immune reconstituted versus non-immune reconstituted HIV-1-infected individuals. We observed that immunological non-responders (INRs) had a low number of DN T cells after long-term antiretroviral therapy (ART) and the number of these cells positively correlated with the CD4+ T cell count. The ART did not result in complete suppression of immune activation recorded by the percentage of CD38+HLA-DR+CD8+T cells in INRs, and a strong inverse correlation was observed between DN T cells and immune activation. A low proportion of TGF-β1+DN T cells was found in INRs. Further mechanism study demonstrated that the level of TGF-β1 producing DN T cells and immune activation had a negative correlation after ART. Taken together, our study suggests that DN T cells control the immunological response in HIV-1-infected patients. These findings expand our understanding of the mechanism of immune reconstitution and could develop specific treatments to return the immune system to homeostasis following initiation of HIV-1 therapy.